Exploring predictors of mothers and children in various work/family situations - Livengood, Jennifer Leigh (Kansas State University, 2010)
Previous literature indicates that individuals tend to believe that a woman who stays at home with a young child is a better mother than a woman who works full time despite having a young child. However, relatively little is known about perceptions of a woman whose work/family status represents a compromise between these two extremes (e.g., a woman who stops working for 18 months after the birth of her child and, then, gradually increases her time at work). Furthermore, prior research has not adequately addressed whether perceptions of mothers in various work/family situations are related to perceptions of their children and their relations with their children. The present study was an attempt to expand the literature by exploring selected individual difference measures as potential predictors of perceptions of mothers in various work-family situations (i.e., Stay-at-Home Mother [SAHM], Working Mother [WM], and Middle Mother [MM]) and by extending the target of these perceptions beyond the mothers to their children and the mother/child relationship. Ninety-six undergraduates (a) completed a series of individual difference measures, (b) were introduced to a WM, SAHM, or a MM via audiotape, (c) observed the mother interact with her child on the identical brief videotape, and (d) rated their perceptions of the mother, child, and mother-child relationship. Contrary to prediction, none of the individual difference measures was associated with any of the participants' attitudinal ratings. However, a consistent pattern was found in which the ratings of the WM, her child, and her relation with her child were less favorable than the respective ratings for the SAHM and MM (which did not differ from one another). The implications and limitations of the present study, as well as a discussion of future directions in research on perceptions of mothers with various work-family situations, are presented.
Keywords: Social Perception; Working Mothers; Psychology, Social (0451)